2018
DOI: 10.1021/jacs.8b04991
|View full text |Cite
|
Sign up to set email alerts
|

H2Oxidation over Supported Au Nanoparticle Catalysts: Evidence for Heterolytic H2Activation at the Metal–Support Interface

Abstract: Water adsorbed at the metal-support interface (MSI) plays an important role in multiple reactions. Due to its importance in CO preferential oxidation (PrOx), we examined H oxidation kinetics in the presence of water over Au/TiO and Au/AlO catalysts, reaching the following mechanistic conclusions: (i) O activation follows a similar mechanism to that proposed in CO oxidation catalysis; (ii) weakly adsorbed HO is a strong reaction inhibitor; (iii) fast H activation occurs at the MSI, and (iv) H activation kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
161
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 155 publications
14
161
0
Order By: Relevance
“…We recently published a detailed study of H 2 dissociative chemisorption using a 1‐D periodic nanorod model; readers are directed there for a full discussion of H 2 adsorption on Au . We extended this study to include homolytic dissociation of H 2 onto the Au 10 /TiO 2 (110) model (the model used above for propyne adsorption).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…We recently published a detailed study of H 2 dissociative chemisorption using a 1‐D periodic nanorod model; readers are directed there for a full discussion of H 2 adsorption on Au . We extended this study to include homolytic dissociation of H 2 onto the Au 10 /TiO 2 (110) model (the model used above for propyne adsorption).…”
Section: Resultssupporting
confidence: 76%
“…The Au 10 cluster likely overestimates binding energies because the individual atoms are more highly uncoordinated than in a 2–3 nm NP. Nevertheless, with the adsorption of 1‐propyne on Au being stronger than both alkyne adsorption on the support (‐34 to −44 kJ/mol, see above) and H 2 adsorption on Au (57 kJ/mol, see Table S22), our simulations suggest that alkynes are likely present on Au sites, even if no IR fingerprint for alkyne adsorption to Au was directly observed.…”
Section: Resultsmentioning
confidence: 99%
“…Related studies have observed similar shifts, however there is no consensus on the direction of the shift, blue or red. In this study, we show how the formation of a metastable gold hydride layer hypothesized by Sil et al ., Silverwood et al ., Whittaker et al . and Ishida et al.,, following H 2 dissociation, explains the blue shift in the dielectric function of the gold‐nanoparticle surface.…”
Section: Introductionsupporting
confidence: 53%
“…Theoretical calculations suggested that the oxygen vacancies are highly reactive toward water dissociation, [38,47] and molecular adsorption on {001} is favored at a relative humidity >34 % . The heterolytic dissociation of H 2 O generates two types of surface OH groups, the O‐containing one is bonded to the Fe atom, and the other one is formed by attaching H to a lattice oxygen . Because of the high relative concentration of coordinately unsaturated Fe sites on α‐Fe 2 O 3 ‐QC (Table ), the π* orbital of CO molecule can easily hybridize the t 2g orbital of Fe, favoring CO adsorption via π‐bonding.…”
Section: Resultsmentioning
confidence: 99%
“…[48] The heterolytic dissociation of H 2 O generates two types of surface OH groups, the Ocontaining one is bonded to the Fe atom, and the other one is formed by attaching H to a lattice oxygen. [48,49] Because of the (Table 3), the π* orbital of CO molecule can easily hybridize the t 2g orbital of Fe, favoring CO adsorption via π-bonding. This may reasonably account for preferential CO adsorption on Au/α-Fe 2 O 3 -QC-Air.…”
Section: Behavior Of Adsorbed H 2 O and Co On The Distinct Interfacesmentioning
confidence: 99%